The Needs of Pedestrian Circulation Design for Adolescents In Semarang Old Town Public Space That Responsive To Covid-19 Pandemic - Nusapatria, Raihan Fanani; Ristianti, Novia Sari (Universitas Negeri Semarang, 2022)
Abstract. Semarang Old Town is a site in Semarang City that provides economically valuable public spaces that teenagers use. Due to irregular pedestrian circulation and packed economic activity points, Semarang Old Town is a sensitive location for the possible spread of the Covid-19 virus. The Covid-19 epidemic has not been addressed in the public spaces of Semarang Old Town. Circulation flow, circulation signage, crossing points, and health protocol facilities have all been identified as issues. This project intends to develop pedestrian circulation needs for teenagers in an economically valuable public place in Semarang Old Town in response to the Covid-19 pandemic. The quantitative method employed in this study was behavior mapping and quantitative descriptive analysis techniques. The stages are as follows: first, identify teenage features; second, analyze design demands for adolescent pedestrian circulation elements. Then, construct the design requirements and placement. The study was conducted on a group of 41 adolescents aged 12 to 25, with observation taking place on Saturday night and Sunday morning (peak hours). According to quantitative descriptive analysis methodologies, adolescents prefer more simple, more adaptable designs and occupy less space by 57 percent..